Design, Modeling, and Comprehensive Analysis for The Wing of an Aircraft - Hakam Waadallah Shehab; Mohammed Saleh Mohammed; Mohammed Najeeb Abdullah (NTU Journal of Engineering and Technology)
This study examines the design and analysis of a training aircraft wing. The methodology includes aerodynamic and stress analyses. Microsoft Excel is utilized for scaling. Aerodynamic forces, load distribution, and air foil comparison computations were performed by Xflr 5. Inventor was used for stress analysis, which yielded wing deflections, Von Mises stresses, and safety factors. AutoCAD was employed to draw wing parts. The proper design for the cross-sectional shape of the inner wing components was determined. The goal is to find the lightest cross-section, the placements and numbers of wing ribs, and calculate the wing's dimensions. The findings revealed that wing tip deflection did not exceed 0.02. The von Mises calculations also show that the chosen material meets the requisite safety factor. For I and U sections, the deflection, von Mises stresses, and safety factor were 46.52mm and 43.27mm, 219.3 MPa and 152.7MPa, and 1.25 and 1.8, respectively.